The Effect of Electronic Money Transactions on Household Consumption - Prihantono, Gigih; Kholifah , Afif Kusnul (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2023)
This study aims to determine the effect of the volume of electronic money transactions on household consumption in Indonesia, Malaysia, Thailand, and Singapore from 2012 to 2019. The seemingly unrelated regression method was chosen due to heteroscedasticity and contemporaneous correlation problems in the model. This method estimates the relationship between the volume of electronic money transactions and household consumption. In this study, electronic money is used in the form of chips and servers. The results of this study indicate that Indonesia, Malaysia, Thailand, and Singapore have a significant positive relationship between the volume of electronic money transactions and household consumption. It indicates that consumers already have confidence in the non-cash payment transaction system, especially electronic money, and feel that using it is more efficient, fast, and secure.